Metodologi Istinbath Hukum Prof. Dr. Wahbah az Zuhaili - Ariyadi Ariyadi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Legal Istinbath Method is How are the discussion of legal sources, methods of legal excavation, and concepts that carry out these legal excavations. Legal sources that discuss are revelation and reality. In a sense, Islam has two references for scientific study, namely; written confessions and unwritten admissions. In the second part, it is not always stagnant, and the substance is still developing when it comes to mistakes, Prof. Dr Wahbah az Zuhaili.